DETERMINAN AUDITOR SWITCHING PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Feliciana; Breliastiti, Ririn (Politeknik Keuangan Negara STAN, 2025)
Abstract: Research objective: This study is intended to examine the impact of company size, audit delay, and audit opinion on auditor switching in infrastructure sector companies listed on the IDX. Method: This research is a quantitative study with secondary data in the form of financial reports of infrastructure sector business entities for the 2019-2023 period selected by applying purposive sampling techniques. The analysis method applied is logistic regression analysis by utilizing SPSS 26 software. Research findings: Based on observations made on 41 infrastructure sector companies for the 2019-2023 period, the research findings show that audit delay and audit opinion partially have a positive effect on auditor switching. Practical implication: Business entities need to pay attention to audit timeliness and optimize the quality of financial statements to obtain an unqualified audit opinion in order to reduce the occurrence of auditor switching in the future which has an impact on public perception. Keywords: Auditor Switching; Company Size; Audit Delay; Audit Opinion; Audit.